Odpowiedzi

Najlepsza Odpowiedź!
2010-03-12T12:52:17+01:00
X/2+2x/3=3/4|*2
x+1⅓x=1,5
2⅓x=1,5
x=⁹/₁₄


5/6x+x/3=3/8|*6
5x+2x=2,25
7x=2,25
x=⁹/₂₈


5x/6-3/5=2x/3|*6
5x-3,6=4x
5x-4x=3,6
x=3,6


x-1/3=0
x=⅓


1/2x-1=29
½x=29+1
½x=30
x=60


x-1/4=x+7/5
5x-5=4x+28
5x-4x=28+5
x=33


0,9x-17=19
0,9x=19+17
0,9x=36
x=40


x+3/5+x+2/2=0,3|*5
x+3+2,5x+5=1,5
3,5x=1,5-3-5
3,5x=-6,5
x=-1⁶/₇


x-2/4-x+3/6=5/12|*4
x-2-⅔x+2=1⅔
x-⅔x=1⅔+2
⅓x=3⅔
x=11


1/2y+6=y-4
½y-y=-4-6
-½y=-10
y=20


2x-8/4-1/5=7x+1/20|*4
2x-8-0,8=1,4x+0,2
2x-1,4x=0,2+8+0,8
0,6x=9
x=15